2016
DOI: 10.1007/s11356-016-7473-8
|View full text |Cite
|
Sign up to set email alerts
|

Determination of 210Po and 210Pb in red-capped scaber (Leccinum aurantiacum): bioconcentration and possible related dose assessment

Abstract: The paper presents the studies on Po andPb activity determination in red-capped scaber (Leccinum aurantiacum (Bulliard) Gray) collected in northern Poland. The aims of the studies were to determine Po andPb content in analyzed mushrooms, evaluate the bioconcentration levels, and estimate possible related annual effective radiation dose to mushrooms consumers. The activities of Po andPb in red-capped scaber were un-uniform and depended on sampling sites. But Po andPb activity concentrations did not reflect thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 23 publications
4
26
0
Order By: Relevance
“…1 and 2 ). The exact procedure for samples preparation for 210 Po and 210 Pb analysis was described by Strumińska-Parulska et al ( 2016 ). The radiochemical analysis of 210 Po included polonium autodeposition on silver discs and its measurement using an alpha spectrometer equipped with semiconductor silicon detectors and a 450-mm 2 active surface barrier (Alpha Analyst S470, Canberra-Packard, USA) according to the method described by Skwarzec ( 1997 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 and 2 ). The exact procedure for samples preparation for 210 Po and 210 Pb analysis was described by Strumińska-Parulska et al ( 2016 ). The radiochemical analysis of 210 Po included polonium autodeposition on silver discs and its measurement using an alpha spectrometer equipped with semiconductor silicon detectors and a 450-mm 2 active surface barrier (Alpha Analyst S470, Canberra-Packard, USA) according to the method described by Skwarzec ( 1997 ).…”
Section: Methodsmentioning
confidence: 99%
“…Frequently studied is 137 Cs that polluted the surface of the Earth due to global radioactive fallout after using and testing of nuclear weapons and from nuclear power plant accidents but also 40 K that is of natural terrestrial origin (Mietelski et al 2010 ; Steinhauser et al 2014 ; Falandysz et al 2016 ; Zalewska et al 2016 ; Falandysz et al 2017d ). Other radionuclides studied in mushrooms included 210 Po, 210 Pb, 234,238 U, 228,230,232 Th, 238 Pu, 239 + 240 Pu (Mietelski et al 2002 ; Vaaramaa et al 2009 ; Guillén and Baeza 2014 ; Strumińska-Parulska et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, locally or regionally, also mushrooms form some other locations in Europe were highly affected (Mietelski et al 2010; Strandberg 2004; Zalewska et al 2016), while in many other sites were much less or little affected (Daillant et al 2013; García et al 2015; Karadeniz and Yaprak 2010; Rakić et al 2014; Turhan et al 2007). From the toxicological point of view, some radioactive compounds other than radiocaesium accumulated by fungi in fruiting bodies can also highly matter, but the number of published data is much less (Kirchner and Daillant 1998; Saniewski et al 2016; Strumińska-Patulska et al 2016). …”
Section: Introductionmentioning
confidence: 99%
“…It should be clear, the lack of statistical difference between both groups is probably related to a small sample size (number of people eating much more seafood products than statistical amount). Some previous studies showed there are some food products estimated as insignificant, that might be an important source of 210 Po and 210 Pb [61][62][63][64][65][66]. The activity concentrations of 210 Pb for analyzed groups were in the range of 1.40 ± 0.11 and 49.6 ± 1.48 Bq kg −1 dry wt.…”
Section: Fish Consumptionmentioning
confidence: 88%